Proving Montessori: Identity and Dilemmas in a Montessori Teacher’s Lived Experience - Christensen, Olivia (Journal of Montessori Research, 2016)
This phenomenological case study was conducted to better understand the experience of a Montessori teacher in a leadership role. A veteran Montessori teacher, newly hired by an established Montessori preschool, was interviewed over the course of her first year in the position. A critical discourse analysis revealed multiple social identities that contributed to her desire, and ability, to be what she felt was an authentic Montessori educator. While some of these discourses and social identities aligned, some did not, creating ideational dilemmas that affected her work, relationships, and personal identity. The findings suggest that current Montessori discourse excludes important characteristics of the teacher-lived experience. Acknowledging and discussing the social challenges Montessori teachers face is a necessary addition to teacher preparation, teacher support systems, and Montessori leadership decisions.